Pengembangan Kurikulum Pendidikan Agama Islam di Pondok Pesantren: Perspektif Teori dan Praktik - Hadi, Moh. Syamsul; Fauzan, Umar; Malihah, Noor (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This article discusses the theory and practices involved in the development of the Islamic religious education curriculum in Islamic boarding schools (pondok pesantren). The curriculum of Islamic religious education in pondok pesantren is an integral part of the Islamic education system, focusing on spiritual, academic, and social education. The main objective of this research is to analyze the theories underlying the development of the Islamic religious education curriculum in pondok pesantren and implement best practices in curriculum development. This article adopts a qualitative approach, collecting data through literature review. The research findings indicate that the development of the Islamic religious education curriculum in pondok pesantren is based on theories of Islamic education, learning theories, and an understanding of the needs of the pesantren students. Successful curriculum development practices include identifying relevant religious competencies, selecting effective teaching methods, developing structured lesson plans, and implementing continuous evaluation to ensure the achievement of learning objectives. The development of the Islamic religious education curriculum in pondok pesantren also involves active participation and engagement from teachers, pondok pesantren administrators, and the pesantren community as a whole. The article emphasizes the importance of considering the local context, culture, and traditions of the pesantren in curriculum development, as well as maintaining a balance between formal education and the transmission of Islamic values through the pesantren tradition. It is expected that this article will provide better insights into the theory and practices of developing the Islamic religious education curriculum in pondok pesantren. By understanding relevant theories and implementing best practices, it is hoped that pondok pesantren can continue to improve the quality of Islamic religious education delivered to the students and produce competent and morally upright graduates.